Argo Observations of the Deep Mixing Band in the Southern Ocean: A Salinity Modeling Challenge. Issue 10 (29th October 2018) - DuVivier, Alice K.; Large, William G.; Small, R. Justin
Abstract: The Southern Ocean plays an important role in mediating oceanic uptake of CO2 and heat due to a strong meridional overturning circulation. Gridded Argo float data for 2004–2017 were used to evaluate subsurface processes at the mixed layer depth (MLD) that occur in a narrow deep mixing band. Shifts in the value of the Turner Angle at the MLD indicate that early in the season the MLD deepens slowly as it encounters and is stabilized by a subsurface salt maximum. By September mixing has penetrated this salinity feature and the rate of deepening is faster once the MLD is deeper than the depth where the maximum salinity occurs ( 150–200 m). This distinctive salinity layer is the result of surface Ekman transport of fresh water from the south and subsurface advection of high‐salinity water from the north. Two configurations of the Community Earth System Model (CESM) ocean‐ice forced hindcast experiments—one with 1° and the other with 0.1° horizontal resolution (Parallel Ocean Program low and high resolutions [POP‐LR and POP‐HR], respectively)—are compared with the Argo data for 2005–2009. POP‐LR has a shallow MLD bias common to many Fifth Coupled Models Intercomparison Project (CMIP5) models, while POP‐HR has a mix of deep and shallow MLD biases. While both models were able to replicate the large‐scale processes leading to formation of a high‐salinity layer, the salinity feature in POP‐HR is too strong and deep. Neither model was able to replicate the vertical mixing processes leading to penetration of the subsurface salt maximum. Plain Language Summary: The Southern Ocean that circles the Antarctic continent is important in controlling the amount of global heat and carbon exchanges with the atmosphere because during the winter the surface waters mix deeply down into the ocean. Argo floats drift throughout the world oceans collecting temperature and salinity data from the surface to about 2, 000‐m depth. This study uses gridded Argo float data for 2004–2017 to understand the vertical mixing. We identify the importance of a subsurface high‐salinity feature in the Southern Ocean that stabilizes the column and impacts the depth of vertical mixing, and we investigate the origin of this salinity feature. We also analyze the representation of the salinity feature in the Community Earth System Model (CESM) at both a coarse and a fine resolution for 2005–2009. We find that both model configurations capture the main processes leading to the formation of the high‐salinity layer. However, neither model configuration was unable to replicate the vertical mixing processes leading to penetration of the subsurface salt maximum. Key Points: Gridded Argo data indicate that a subsurface salinity maximum mediates the rate of mixed layer deepening Turner angle at the mixed layer depth provides a useful metric to evaluate the impact of salinity on stability Neither coarse nor fine‐resolution models can consistently replicate the processes necessary to penetrate the salinity feature